Shame, Stigma and Indebtedness in Gambling-Related Harm: A Rapid Review of Help-Seeking and Suicidality - Sharon Mallon; Jessica Runacres; Fiona McCormack; Victoria Riley; Emily Motta-Yanac (International Journal of Environmental Research and Public Health, 2026)
Background: Gambling-related harm is recognised as a public health concern, yet limited synthesis has examined how shame, stigma and indebtedness shape help-seeking and suicidality across gendered and cultural contexts. This review addressed the following question: among individuals experiencing gambling-related harms, how do cultural and gender-based understandings of shame and indebtedness influence suicidality and help-seeking across diverse settings? Methods: This rapid review searched MEDLINE, PsycINFO and CINAHL, alongside grey-literature and reference-list searches, for studies since 2000. Included studies were appraised (CASP, MMAT, or MQC-SP) and synthesised narratively. Results: Twenty-six qualitative, quantitative and mixed-methods studies were included. Gambling was portrayed as socially embedded and normalised, while gambling-related harm remained associated with judgement. Shame was linked to concealment, self-management and delayed disclosure. Indebtedness was associated with concealment, relationship strain, and sometimes made previously hidden gambling-related harm visible; however, the evidence did not allow firm conclusions about its relationship with crisis or suicidality. Help-seeking commonly occurred after harms had escalated and was facilitated by confidential, non-judgemental and culturally appropriate support. Gender and culture shaped meanings of responsibility, control, family reputation and disclosure, but were rarely examined analytically. Conclusions: Public health responses should improve early recognition of gambling-related harm through clear, non-judgemental messaging and stronger links between support services. Further research should clarify how shame, stigma and indebtedness relate to disclosure and suicidal distress, and should evaluate public health messaging, early-support routes, self-directed interventions and support for affected others.